Microglia activation in central nervous system disorders: A review of recent mechanistic investigations and development efforts - Qin, Jun; Ma, Zhihui; Chen, Xiaoli; Shu, Shiyu (Frontiers in Neurology, 2023)
Microglia are the principal resident immune cells in the central nervous system (CNS) and play important roles in the development of CNS disorders. In recent years, there have been significant developments in our understanding of microglia, and we now have greater insight into the temporal and spatial patterns of microglia activation in a variety of CNS disorders, as well as the interactions between microglia and neurons. A variety of signaling pathways have been implicated. However, to date, all published clinical trials have failed to demonstrate efficacy over placebo. This review summarizes the results of recent important studies and attempts to provide a mechanistic view of microglia activation, inflammation, tissue repair, and CNS disorders.